Aesthetic Perception in Kurdish Theatrical Performance - A Case Study of the Play (The Continuous Story) - Bayar Lois Yaqoob; Balqees Ali Aldoski (Zanco Journal of Humanity Sciences)
Theatrical art and philosophy have a complementary, multidimensional relationship, in that they explore fundamental questions about the human condition and the nature of reality. Therefore, this research is a study to understand the philosophical-aesthetic dimension of presenting the play (The Continuing Story) from Kurdish culture, written and directed by (Ahmed Salar), with the aim of answering the question (What are the aesthetic concepts that are observed in the presentation of the play (The Continuing Story)?) In the theoretical framework, some of the aesthetic ideas of art were discussed, and then these different ideas and their impact on the presentation sample were analyzed, to conclude that: